Beyond the Principle of Responsibility. The Schizophrenic Gospel by Bohumil Hrabal Interpreted by Józef Tischner - Firlej, Agata (Poznańskie Studia Slawistyczne, 2022)
The article is devoted to the story The Schizophrenic Gospel by Bohumil Hrabal and a little-known interpretation of this prose bythe famous Polish philosopher and theologian Józef Tischner. Plato, Hegel, Berkeley, Heidegger: these four names in Tischner‘s work lead to Hrabal‘s thinking and his gospel. The philosopher discusses in detail the specific perception of reality which according to him is transformed into a phenomenon or image of reality in Hrabal‘s prose, and as such acquires the same status as the reality of a dream. This approach can be combined with surrealism and phenomenology. Philosophy and literature evaluate the most phenomena irreversibly and undeniably; recurring events and events that do not involve visible changes or consequences are usually neglected. They do not require answers, so they do not mean responsibility. Hrabal writes about such aworld “outside the principle of responsibility“ in his Gospel, and Tischner in his interpretation.